MODELS OF UNIVERSITY AUTONOMY IN EU COUNTRIES: COMPARATIVE ANALYSIS - Oksana Bulvinska (Неперервна професійна освіта: теорія та практика)
The article is devoted to justifying the classification of models of university autonomy based on their comparative analysis. It is emphasized that education functions as a systemic element in the social structure, which is embedded in connections and coordination with other social actors, in particular with state power and the market. It is noted that university autonomy is the authority of a higher education institution to determine its own goals and programs, as well as the means to achieve them; autonomy, independence and responsibility in making decisions regarding one's own development. It is emphasized that the degree of university autonomy is correlated with the country's political and administrative system, economic development and cultural traditions, historical and ideological context, axiological orientation of society, traditional role of higher education institutions. On the basis of a comparative analysis of common features and specifics of models of university autonomy, the author's classification is substantiated depending on three fundamental factors: relations between state authorities and universities; internal organizational and management structure of universities; as well as generalization of cases of certain national systems of higher education or groups of countries united by historical and regional features. It is emphasized that the most relevant is the classification of models of university autonomy, which takes into account not only the relationship between state control and university autonomy and the peculiarities of intra-university management, but also the administrative and financial system of the state, financial support of higher education, etc.